Brand Equity, Product Variation, Social Influence, and Halal Labeling on the Interest in Buying Wardah Lipstick Cosmetics Among Women in Pekanbaru City - Amin, Amirudin M.; Harahap, Dinda Rezki (First Ciera Publisher, 2024)
This research aims to determine and analyze the influence of brand equity, product variety, social influence, and halal labeling on interest in buying cosmetics. This research was conducted in Pekanbaru City. Determining the sample in this study used the Purposive Sampling method with 150 respondents. The population used is all consumers in Pekanbaru City. Data analysis using multiple linear regression. The results of the research show that there is no significant and negative influence between brand equity on purchasing interest, and there is a positive and significant influence between product variety on purchasing interest, and there is no significant and negative influence between social influence and halal labeling on purchasing interest.